Study on Seed Dormancy and Germination Characteristics of Portulaca pilosa - Gong, Jiajian; Yang, Xiaofeng; Xing, Gucai; Lin, Huishan (Asian agricultural research, 2016)
To improve understanding of Portulaca pilosa seed germination and lay technical foundation for seedling cultivation,this paper studies the characteristics of dormancy and germination of Portulaca pilosa seed. Research indicates that its primary seed dormancy period is about25 d,dormancy can be completely released by storage at room temperature for 30 d; the seed is positively photoblastic seed that can’t sprout and can be induced into dormancy in low light conditions; the dormancy-released seed is more sensitive to light when compared with the freshly picked seed,and the germination peak arises 1 d earlier; Portulaca pilosa seed favorites humid conditions,and the higher the soil moisture,the higher the germination rate and germination energy of the seed. The dormancy-released seeds should be used for Portulaca pilosa seedling cultivation,and after the germination is accelerated for 2- 3 d in the light conditions,the seeds are sown on the soil surface,and covered with transparent plastic film to keep moisture and light,which is conducive to the emergence of seeds.